Keeping it Clean: Plan Your Cleaning - Mary N. Harrison (EDIS, 2019)
This document is FCS5232-02, one of a series on Home Cleaning and Repairing of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.